3D Inversion of Airborne Magnetic Data and Validation of it by Using Sourk Mine Drilling Data (Nexo Revista Científica, 2021)
The airborne magnetic method is one of the most significantly applied approaches in mineral exploration. This magnetic method has been widely used in recent years due to its extensive coverage, lower cost than other methods and coverage of impassable areas and forests. For many years in Iran, the magnetic method has been utilized by authorities to survey ore deposits and to prepare structural and geological maps. This paper presents part of the Dehshir area exploration data of airborne surveys by helicopter with flight line spacing of 250 meters and flight height of 40 meters conducted by Geological Survey and Mineral Exploration of Iran. Furthermore, among the potential areas in the Dehshir area is the studied hereby area of Block C2 of Sourk mine. This region in Yazd province with a 4.1 km2 area is located at 95 km northwest of Yazd city. The purpose of this paper is to present a three-dimensional model of magnetic data and its validation using drilling data. The three-dimensional modeling of magnetic data has been processed by Inversion method. Next, the locations of boreholes were proposed for drilling. Then, the boreholes data is used to evaluate the geophysical method model by comparing the three-dimensional modeling of magnetic data and three-dimensional modeling of the proposed drilled boreholes data.